1997
DOI: 10.1172/jci119241
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring mutations in the human 5-lipoxygenase gene promoter that modify transcription factor binding and reporter gene transcription.

Abstract: Five lipoxygenase (5-LO) is the first committed enzyme in the metabolic pathway leading to the synthesis of the leukotrienes. We examined genomic DNA isolated from 25 normal subjects and 31 patients with asthma (6 of whom had aspirin-sensitive asthma) for mutations in the known transcription factor binding regions and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
161
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 316 publications
(168 citation statements)
references
References 22 publications
6
161
0
1
Order By: Relevance
“…À1708G/A (no rs available designation) Modifying gene transcription with an increased protein expression (In et al, 1997) release of IL-10 observed in these high (+896A+) responder cell cultures (n = 10, r = À0.203, p = 0.023, data not shown). Thus, the possible reasons for this correlation might be the important contribution of biological effect of the SNP.…”
Section: -Lo (Nm-000698)mentioning
confidence: 99%
See 1 more Smart Citation
“…À1708G/A (no rs available designation) Modifying gene transcription with an increased protein expression (In et al, 1997) release of IL-10 observed in these high (+896A+) responder cell cultures (n = 10, r = À0.203, p = 0.023, data not shown). Thus, the possible reasons for this correlation might be the important contribution of biological effect of the SNP.…”
Section: -Lo (Nm-000698)mentioning
confidence: 99%
“…Changes in eicosanoid levels are also correlated with SNPs in the promoter region of PTGS2 and 5-Lo genes, respectively codifying the cyclooxygenase-(Cox)-2 and 5-lipoxygenase (5-Lo), enzymes involved in arachidonic acid metabolism. Two functional (À765G/C PTGS2 and À1708G/A 5-Lo) SNPs have recently been identified and associated with the major age-related diseases (Candore et al, 2007a,b;Caruso et al, 2009;Cipollone et al, 2004;In et al, 1997;Orbe et al, 2006). To clarify and confirm the possible pathophysiological effects of +896A/G TLR4 SNP (Balistreri et al, 2004(Balistreri et al, , 2010, we analysed the levels of IL-6, TNF-a, IL-10 and eicosanoids (LTB4 and PGE2) in LPS-stimulated whole blood samples in vitro of 50 young healthy Sicilians, screened for the presence of +896A/G TLR4 SNP.…”
Section: Introductionmentioning
confidence: 99%
“…The ALOX5 5¢UTR has been well characterised and by resequencing asthma patient DNA samples mutations in the region 176-146 bp upstream of the ATG (in a GC-rich region) with deletion of one, or two or addition of one zinc finger (Sp1/Egr-1) binding sites have been identified which results in reduced Sp1/Egr-1 transcription factor binding and gene transcription (103,104). Mutations of the Sp1 repeat in the promoter are associated with airway hyperresponsiveness, but not asthma susceptibility (105,106).…”
Section: Alox5 and Alox5apmentioning
confidence: 99%
“…In et al (1997) first identified the promoter polymorphism of the ALOX5 gene consisting of a variable number of tandem repeats of GC-rich motifs associated with the binding of Sp1 transcription factors subjects with the wildtype genotype (five repeats) had a significantly higher capacity to produce Cys-LTs compared to those with a mutant genotype (3, 4, or 6 repeats). Furthermore, a significant association between the ALOX5 promoter polymorphism and the severity of airway hyperresponsiveness was detected in a Korean population (Kim et al 2005); When we screened ten SNPs for key enzymes involved in arachidonate metabolism, 5-lipoxygenase ( A L O X 5 , -1 7 0 8 G > A , 2 1 C > T, 2 7 0 G > A , 1 7 2 8 G > A ) , A L O X 5 -a c t i v a t i n g p r o t e i n (ALOX5AP, 218A>G), and cyclooxygenase 2 (COX-2, -162C>G, 10T>G, 228G>A), in a Korean population, the lack of an association was noted between the ALOX5AP, COX-2, and CYSLTR1 gene polymorphisms, and the AIA phenotype (Choi et al 2004).…”
Section: Discussionmentioning
confidence: 99%